Determination of possible microRNA-markers of cobalt abuse by real-time qPCR using hypoxia signaling pathway panels - P. V. Postnikov; F. V. Radus; Yu. A. Efimova; I. V. Pronina (Тонкие химические технологии)
Objectives. Cobalt mimics the state of hypoxia to prevent degradation of the alpha subunit of hypoxia-inducible factor, resulting in an increase in blood oxygen capacity and endurance. Athletes can use this property to gain competitive advantage. Nowadays, direct methods of inductively coupled plasma mass spectrometry and liquid chromatography-tandem mass spectrometry are used to determine total cobalt levels in the body. However, the World Anti-Doping Agency is yet to establish a maximum allowable threshold concentration of this element in biofluids. The lack of clear identification criteria complicates the interpretation of the obtained results for the purposes of doping control. In this regard, the present work proposes a new approach for the indirect determination of possible cobalt abuse based on changes in the expression levels of miRNAs involved in the regulation of hypoxia signaling pathways. Here, the aim is to identify possible microRNA markers whose expression does not depend on exercise-induced hypoxia, but changes markedly when taking cobalt preparations.Methods. MicroRNA isolation was performed from blood plasma samples using the PAXgene Blood miRNA Kit. Quantitative real-time polymerase chain reaction (PCR) was performed on CFX96 Bio-Rad (USA) analyzer using miScript® SYBR® Green PCR Kits and panels for studying the expression profiles of mature microRNAs of the hypoxia signaling pathway miScript® miRNA PCR Array.Results. Based on the statistical analysis of the data, it was found that the expression of hsa-miR-15b-5p in the blood plasma of the subjects does not depend on physical activity, but increases when taking cobalt preparations.Conclusions. The difference in expression levels during anaerobic exercise-induced hypoxia and cobalt-induced hypoxia makes hsa-miR-15b-5p a potential candidate to be a marker of erythropoiesis-stimulating agent abuse.